2007
DOI: 10.1590/s1679-87592007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Auto- and heterotrophic nanoplankton and filamentous bacteria of Guanabara Bay (RJ, Brazil): estimates of cell/filament numbers versus carbon content

Abstract: Variations of nanoplankton (2-20 µm) and filamentous bacteria (diameter: 0.5-2.0 µm) of Guanabara Bay (RJ, Brazil) are presented, considering cell density and carbon content of auto- and heterotrophs. Our goal is to contribute to future modeling of local trophic dynamics. Subsurface water samples were taken weekly during the year 2000 at two sites: Urca (close to the entrance, more saline, eutrophic) and Ramos (inner area, less saline, hypertrophic). Microscopic analysis was done by epifluorescence and cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…The low frequency and abundance of Skeletonema costatum called the authors' attention since this diatom has been consistently reported as opportunist in eutrophic environments. This pattern change may be associated with the location of the sampling stations close to the bay's entrance, a less polluted site due to the contribution of more saline, cleaner and clearer coastal water (SANTOS et al, 2007). Similar results were found by GUENTHER et al (2012) in a short temporal scale investigation also in the entrance of Guanabara Bay during summer 2004, in which S. costatum was not considered an abundant taxon.…”
Section: Discussionsupporting
confidence: 68%
“…The low frequency and abundance of Skeletonema costatum called the authors' attention since this diatom has been consistently reported as opportunist in eutrophic environments. This pattern change may be associated with the location of the sampling stations close to the bay's entrance, a less polluted site due to the contribution of more saline, cleaner and clearer coastal water (SANTOS et al, 2007). Similar results were found by GUENTHER et al (2012) in a short temporal scale investigation also in the entrance of Guanabara Bay during summer 2004, in which S. costatum was not considered an abundant taxon.…”
Section: Discussionsupporting
confidence: 68%
“…The driving phytoplankton assemblages of Guanabara Bay are typical for eutrophic to hypertrophic systems that are largely dominated by bloom and also red tide forming nanoplankton, filamentous cyanobacteria and some microplankton (Valentin et al, 1999;Santos et al, 2007;Villac and Tennenbaum, 2010). Preliminary investigations of the collected material from this study suggests that cyanobacteria were frequently encountered in S2, S4 and S5 during the nine sampling periods, and a great deal of patchiness was observed with a succession of intense red-, brown-and/or green-coloured waters, leading to the marked short spatial variability in pCO 2 , DO and Chl a.…”
Section: Eutrophication and Co 2 Dynamicsmentioning
confidence: 99%
“…The plankton communities of Guanabara Bay have been well studied since the beginning of the XXth century on both short and long term scales, providing a relevant array of information about the dynamics of the autotrophic microplankton (VILLAC; TENENBAUM, 2010 and references therein), bacterioplankton (GUENTHER et al, 2008b), auto-and heterotrophic nanoplankton , microzooplankton (GOMES et al, 2007) and mesozooplankton (e.g. WANDERNESS et al, 1997;VALENTIN et al, 1999;GOMES et al, 2004;SCHWAMBORN et al, 2004). Nevertheless, none of them has yet evaluated the dynamics of the auto-and heterotrophic plankton compartments simultaneously.…”
Section: Introductionmentioning
confidence: 99%